Integrative taxonomy in the genus Rhabdias Stiles et Hassall, 1905 from anuran in Brazil, description of two new species and phylogenetic analyses - Alcantara, Edna Paulino [UNESP]; Müller, Maria Isabel; Úngari, Leticia Pereira [UNESP]; Ferreira-Silva, Cristiana [UNESP]; Emmerich, Enzo [UNESP]; Giese, Elane Guerreiro; Morais, Drausio Honorio; Santos, André Luiz Quagliatto; O'Dwyer, Lucia Helena [UNESP]; Silva, Reinaldo José [UNESP] (Elsevier, 2023)
About 20 valid species of the genus Rhabdias are known in the Neotropical region. The present study aimed to describe two new species of Rhabdias parasitizing the lungs of Leptodactylus macrosternum and Leptodactylus podicipinus from Brazil. Distinctive characteristics between these species are numerous and based on body size, size of the buccal capsule, shape and size of the oesophagus, and position of the vulva. Molecular data based on ribosomal genes 28S and ITS region and mitochondrial COI of the two species are presented. Molecular analysis and comparison of the partial mitochondrial COI sequence of Rhabdias matogrossensis n. sp. and Rhabdias guaianensis n. sp. revealed a genetic divergence between these new species and the sequences of Rhabdias spp. previously deposited in GenBank. In the phylogenetic analysis, R. matogrossensis n. sp. was grouped with R. breviensis species complex, and R. guaianensis n. sp. was grouped as a sister group of R. cf. stenochepala. This study contributes to improving the diversity of known species of Rhabdias described in Brazilian anurans.
Keywords: Anura; Molecular identification; Morphology; Nematoda; Taxonomy